2019
DOI: 10.1186/s42506-019-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life and factors associated with it among nurses in public hospitals, Iran

Abstract: Background: There is an acute shortage of nurses worldwide including Iran. Quality of work life is important for nurses as it affects the safety and quality of care provided for patients as well as organizational factors. The aim of this study was to describe the status of quality of work life and to explore its predictors among nurses in Iran. Methods: A cross-sectional study was conducted on 2391 nurses in 85 Iranian public hospitals, selected through the convenience sampling. Data were collected using demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 37 publications
11
78
2
6
Order By: Relevance
“…This finding is in line with studies conducted in Jorden, South Ethiopia, and Turkey [16, 20,22]. However, in other studies, older nurses have a substantially higher average quality of work life ratings than younger nurses [24]. Regarding gender, [8,24] reported male nurses had a lower average of QNWL levels than female participants, which was…”
Section: Demographic Characteristic and Pos And Qnwlsupporting
confidence: 88%
See 4 more Smart Citations
“…This finding is in line with studies conducted in Jorden, South Ethiopia, and Turkey [16, 20,22]. However, in other studies, older nurses have a substantially higher average quality of work life ratings than younger nurses [24]. Regarding gender, [8,24] reported male nurses had a lower average of QNWL levels than female participants, which was…”
Section: Demographic Characteristic and Pos And Qnwlsupporting
confidence: 88%
“…It is in line with other study findings [16,22] Concerning marital status, there was no correlation between QNWL and marital status in the current study result, and this similarity to the study conducted by [16,22,23]. This result was inconsistent with the research reported that single nurses had significantly lower average scores of QNWL [8,24]. Moreover, recent study have shown that highly qualified nurses are more satisfied with their quality of work life [24].…”
Section: Relationship Between Perceived Organizational Support and Qusupporting
confidence: 69%
See 3 more Smart Citations